Neurofilament light is a treatment‐responsive biomarker in CLN2 disease. Issue 12 (8th December 2019) - Ru, Yuanbin; Corado, Carley; Soon, Russell K.; Melton, Andrew C.; Harris, Adam; Yu, Guoying K.; Pryer, Nancy; Sinclair, John R.; Katz, Martin L.; Ajayi, Temitayo; Jacoby, David; Russell, Chris B.; et al.
Abstract: Objective: Neuronal ceroid lipofuscinosis type 2 (CLN2 disease) is a rare, progressive, fatal neurodegenerative pediatric disorder resulting from deficiencies of the lysosomal enzyme tripeptidyl peptidase 1 that are caused by mutations in TPP1 . Identifying biomarkers of CLN2 disease progression will be important in assessing the efficacy of therapeutic interventions for this disorder. Neurofilament light is an intrinsic component of healthy neurons; elevated circulating extracellular neurofilament light is a biomarker of neuropathology in several adult‐onset neurological diseases. Our objective was to assess whether circulating neurofilament light is a biomarker that is responsive to enzyme replacement therapy (ERT) in CLN2 disease. Methods: Using an ultrasensitive immunoassay, we assessed plasma neurofilament light changes during disease progression in a canine model of CLN2 disease and in ERT clinical trial CLN2 disease patients. Results: In tripeptidyl peptidase 1 ( TPP1 )‐null dogs ( N = 11), but not in control dogs [ N = 6 ( TPP1 +/− ) and N = 27 (WT)], neurofilament light levels increased more than tenfold above initial low baseline levels during disease progression. Before treatment in 21 human subjects with CLN2 disease (age range: 1.72–6.85 years), neurofilament light levels were 48‐fold higher ( P < 0.001) than in 7 pediatric controls (age range: 8–11 years). Pretreatment neurofilament light did not significantly correlate with disease severity or age. In CLN2 disease subjects receiving ERT, neurofilament light levels decreased by 50% each year over more than 3 years of treatment. Interpretation: Our data indicate that circulating neurofilament light is a treatment‐responsive biomarker in CLN2 disease and could contribute to understanding of the pathophysiology of this devastating pediatric disorder.